Composite photocatalyst as well as preparation method and application thereof

By growing CuCo2O4 and BiOF in situ on the CuBi2O4 surface, a multi-load ion shunt channel was constructed, which solved the problem of slow carrier transfer of CuBi2O4 material, significantly improved the catalytic activity and degradation efficiency of the composite photocatalyst, and achieved efficient pollutants degradation.

CN119114113APending Publication Date: 2024-12-13TAIZHOU UNIV (ZHEJIANG)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411258970.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The slow carrier transfer and carrier surface recombination of the single-component CuBi2O4 material seriously limit its application efficiency in pollutant degradation, and the catalytic degradation efficiency of existing composite photocatalysts are still not sufficient to meet actual needs.

Method used

By growing CuCo2O4 and BiOF in situ on the CuBi2O4 surface, a dual interface structure and multi-load ion shunt channel are constructed to improve the transmission path and catalytic activity of photogenerated carriers, and a tight interface is formed to promote efficient carrier separation and reaction.

Benefits of technology

The 90.3% degradation rate of tetracycline hydrochloride was achieved within 15 minutes, which significantly improved the catalytic activity and efficiency of the composite photocatalyst to meet the actual application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005035023010000011
    Figure HDA0005035023010000011
  • Figure HDA0005035023010000012
    Figure HDA0005035023010000012
  • Figure HDA0005035023010000013
    Figure HDA0005035023010000013
Patent Text Reader

Abstract

The invention provides a composite photocatalyst as well as a preparation method and application thereof, and belongs to the technical field of photocatalysis. The composite photocatalyst provided by the invention comprises CuBi2O4, CuCo2O4 and BiOF, wherein the CuCo2O4 and the BiOF grow on the CuBi2O4 in situ. CuCo2O4 and BiOF are introduced to the surface of CuBi2O4, and a dual-interface structure is formed among the three components, so that a multi-heavy-load ion shunting channel is constructed, and the catalytic activity and catalytic efficiency of the composite photocatalyst are improved; meanwhile, CuCo2O4 and BiOF which grow in situ have a closer interface with CuBi2O4, efficient separation of current carriers is promoted, and the composite photocatalyst has excellent photocatalytic activity and high catalytic efficiency. The data of the embodiment shows that the degradation rate of the tetracycline hydrochloride can reach 90.3% after the tetracycline hydrochloride is catalytically degraded by the composite photocatalyst provided by the invention within 15 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis technology, and in particular to a composite photocatalyst and a preparation method and application thereof. Background Art

[0002] Composite photocatalysts are widely used in sterilization, sewage treatment, soil remediation and other fields due to their excellent photocatalytic activity, good stability and versatility. The catalytic activity of composite photocatalysts is often affected by the interface carrier separation mode and separation efficiency. There are three common carrier separation modes: Type I, Type II and S-type carrier separation. Among the above three carrier separation modes, the S-type carrier separation mode has attracted much attention because it can enable the catalytic system to have excellent photogenerated carrier separation ability and strong redox ability. Composite systems with S-type carrier separation mode are often composed of reduced semiconductors and oxidized semiconductors. Under illumination conditions, the photogenerated electrons on the conduction band of the oxidized semiconductor will recombine with the holes on the valence band of the reduced semiconductor, thereby retaining the useful photogenerated electrons and holes on the conduction band and valence band of the reduced semiconductor and the oxidized semiconductor, respectively, which not only realizes efficient carrier separation, but also makes the carriers have strong redox ability.

[0003] CuBi2O4 is a p-type reduced semiconductor material with a spinel structure. It has the advantages of strong light absorption, narrow band gap, suitable energy band position and stable physical and chemical properties. It is widely used in pollutant degradation. However, single-component CuBi2O4 has bottleneck problems such as slow carrier transport and severe carrier surface recombination, which greatly limits the application of this material. CuCo2O4 material is a bimetallic oxide with a spinel structure, which usually has high conductivity and catalytic activity; due to its low band gap position, it is a more ideal oxidized semiconductor. Coupling reduced CuBi2O4 with oxidized CuCo2O4 is expected to construct a heterogeneous catalyst with S-type carrier separation and improve the catalytic activity of the photocatalyst. For example, the prior art provides a CuBi2O4 / CuWO4 composite photocatalyst obtained by coupling reduced CuBi2O4 and oxidized CuWO4. The composite photocatalyst is used to degrade tetracycline hydrochloride. Although the degradation rate can be as high as about 90%, it takes 120 minutes to reach the highest degradation rate of tetracycline hydrochloride; the catalytic degradation efficiency of the composite photocatalyst still cannot meet the needs of practical applications. Summary of the invention

[0004] The purpose of the present invention is to provide a composite photocatalyst and a preparation method and application thereof. The composite photocatalyst provided by the present invention has excellent photocatalytic activity and high catalytic efficiency.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a composite photocatalyst, comprising CuBi2O4 and CuCo2O4 and BiOF in-situ grown on the CuBi2O4.

[0007] Preferably, the CuBi2O4 is a nanorod; the length of the nanorod is 200nm to 3μm, and the diameter is 30 to 70nm.

[0008] The present invention also provides a method for preparing the composite photocatalyst described in the above technical solution, comprising the following steps:

[0009] (1) mixing CuBi2O4 with a copper source, a cobalt source, urea, ammonium fluoride and a solvent to obtain a mixed solution;

[0010] (2) subjecting the mixed solution obtained in step (1) to a solvothermal reaction to obtain a precursor;

[0011] (3) calcining the precursor obtained in step (2) to obtain a composite photocatalyst.

[0012] Preferably, the molar ratio of CuBi2O4, copper source, cobalt source and urea in step (1) is 1:(1-3):(4-6):(1-3).

[0013] Preferably, the ratio of the amount of CuBi2O4 in step (1) to the volume of the solvent is (1-5) mmol:40 mL.

[0014] Preferably, the concentration of ammonium fluoride in the mixed solution in step (1) is 5.0 to 30 mmol / L.

[0015] Preferably, the temperature of the solvent thermal reaction in step (2) is 100 to 180° C., and the time of the dissolution thermal reaction is 2 to 24 hours.

[0016] Preferably, in step (3), the calcination temperature is 300-500° C., the calcination heating rate is 1-10° C. / min, and the calcination time is 0.5-8 h.

[0017] The present invention also provides the use of the composite photocatalyst described in the above technical solution or the composite photocatalyst prepared by the preparation method described in the above technical solution in catalytic degradation of organic pollutants in sewage.

[0018] Preferably, the dosage of the composite photocatalyst is 1-5 g / L.

[0019] The present invention provides a composite photocatalyst, comprising CuBi2O4 and CuCo2O4 and BiOF in situ grown on the CuBi2O4. The present invention introduces CuCo2O4 and BiOF on the surface of CuBi2O4 to form a double interface structure between the three components, thereby constructing multiple ion-carrier shunt channels, providing more transmission paths for photogenerated carriers, enabling photogenerated carriers to migrate to the reaction active sites of the catalyst more quickly and effectively, and improving the catalytic activity and catalytic efficiency of the composite photocatalyst; at the same time, these separation channels can also increase the specific surface area of ​​the composite photocatalyst and expose more active sites; multiple carrier separation channels can also avoid recombination after the generation of photogenerated carriers, and further improve the catalytic performance of the composite photocatalyst; and the in situ grown CuCo2O4 and BiOF have a tighter interface with CuBi2O4, so that there is a stronger interaction between the interfaces, promoting the efficient separation of carriers, and making the composite photocatalyst have excellent photocatalytic activity and high catalytic efficiency. The data in the examples show that the composite photocatalyst provided by the present invention can achieve a degradation rate of 90.3% for catalytic degradation of tetracycline hydrochloride within 15 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the CuCo2O4 / BiOF / CuBi2O4 composite photocatalyst of Example 1 of the present invention;

[0021] Figure 2 This is a SEM image of the CuCo2O4 / BiOF / CuBi2O4 composite photocatalyst of Example 2 of the present invention;

[0022] Figure 3 This is a SEM image of the CuCo2O4 / BiOF / CuBi2O4 composite photocatalyst of Example 3 of the present invention;

[0023] Figure 4 XRD diagrams of the CuCo2O4 / BiOF / CuBi2O4 composite photocatalyst of Example 2 of the present invention, the CuBi2O4 photocatalyst of Comparative Example 1, and the CuCo2O4 photocatalyst of Comparative Example 2;

[0024] Figure 5 This is a graph showing the catalytic activity of the CuCo2O4 / BiOF / CuBi2O4 composite photocatalysts of Examples 1 to 3 of the present invention, the CuBi2O4 photocatalyst of Comparative Example 1, and the CuCo2O4 photocatalyst of Comparative Example 2 to tetracycline hydrochloride. DETAILED DESCRIPTION

[0025] The invention provides a composite photocatalyst, comprising CuBi2O4 and CuCo2O4 and BiOF in-situ grown on the CuBi2O4.

[0026] The composite photocatalyst provided by the present invention includes CuBi2O4. In the present invention, CuBi2O4 not only plays a photocatalytic role, but also serves as a matrix for the in-situ growth of CuCo2O4 and BiOF, thereby ensuring the formation of the composite photocatalyst.

[0027] In the present invention, the CuBi2O4 is preferably a nanorod; the length of the nanorod is preferably 200nm~3μm, more preferably 500nm~2μm, most preferably 800nm~1μm; the diameter of the nanorod is preferably 30~70nm, more preferably 40~60nm, most preferably 50~55nm.

[0028] The composite photocatalyst provided by the present invention also includes CuCo2O4 and BiOF. In the present invention, CuCo2O4 and BiOF are in situ grown on CuBi2O4, so that the composite material has a tighter interface, the interfaces have stronger interactions, the efficient separation of carriers is promoted, and the catalytic performance of the composite photocatalyst is improved.

[0029] The composite photocatalyst provided by the present invention forms a double interface structure between the three components by introducing CuCo2O4 and BiOF on the surface of CuBi2O4, thereby constructing multiple ion-carrier diversion channels, providing more transmission paths for photogenerated carriers, so that the photogenerated carriers can migrate to the reaction active sites of the catalyst more quickly and effectively; at the same time, these separation channels can also increase the specific surface area of ​​the composite photocatalyst and expose more active sites; multiple carrier separation channels can also avoid recombination after the generation of photogenerated carriers, further improving the catalytic performance of the composite photocatalyst.

[0030] The present invention also provides a method for preparing the composite photocatalyst described in the above technical solution, comprising the following steps:

[0031] (1) mixing CuBi2O4 with a copper source, a cobalt source, urea, ammonium fluoride and a solvent to obtain a mixed solution;

[0032] (2) subjecting the mixed solution obtained in step (1) to a solvothermal reaction to obtain a precursor;

[0033] (3) calcining the precursor obtained in step (2) to obtain a composite photocatalyst.

[0034] The invention mixes CuBi2O4 with a copper source, a cobalt source, urea, ammonium fluoride and a solvent to obtain a mixed solution.

[0035] In the present invention, the CuBi2O4 is preferably a nanorod; the length of the nanorod is preferably 200nm~3μm, more preferably 500nm~2μm, most preferably 800nm~1μm; the diameter of the nanorod is preferably 30~70nm, more preferably 40~60nm, most preferably 50~55nm.

[0036] In the present invention, the preparation method of CuBi2O4 preferably includes: mixing a first copper source, a bismuth source, an alkali and water, and performing a hydrothermal reaction to obtain CuBi2O4.

[0037] In the present invention, the first copper source is preferably copper nitrate or copper sulfate, more preferably copper nitrate. In the present invention, the first copper source provides Cu element as a raw material for synthesizing CuBi2O4.

[0038] In the present invention, the bismuth source is preferably bismuth nitrate or bismuth chloride, more preferably bismuth nitrate. In the present invention, the bismuth source provides Bi element as a raw material for synthesizing CuBi2O4.

[0039] In the present invention, the base is preferably sodium hydroxide or potassium hydroxide, more preferably sodium hydroxide. In the present invention, the base provides an alkaline environment to promote the hydrolysis of the first copper source and the bismuth source to form corresponding intermediates, thereby reacting to obtain CuBi2O4.

[0040] In the present invention, the molar ratio of the first copper source, bismuth source and base is preferably 1:2:(7-10), more preferably 1:2:(8-9), and most preferably 1:2:9; the molar ratio of the first copper source to the volume of water is preferably 1mmol:(37.5-80)mL, more preferably 1mmol:(37.5-60)mL, and most preferably 1mmol:37.5mL. In the present invention, by limiting the dosage ratio and concentration of the first copper source, bismuth source and base, the reaction is ensured to proceed smoothly to obtain CuBi2O4, the formation of by-products and other impurity phases is avoided, relatively pure raw materials are provided for the subsequent composite photocatalyst, and the catalytic performance of the composite photocatalyst is further improved.

[0041] In the present invention, the mixing is preferably stirring and mixing; the present invention has no special limitation on the stirring and mixing, and the first copper source, bismuth source and alkali of the reaction raw materials can be mixed and mixed with water.

[0042] In the present invention, the temperature of the hydrothermal reaction is preferably 150-220°C, more preferably 160-200°C, and most preferably 180°C; the time of the hydrothermal reaction is preferably 9-48h, more preferably 15-36h, and most preferably 24h. In the present invention, by controlling the process parameters of the hydrothermal reaction, the chemical reaction between the first copper source and the bismuth source is ensured to proceed smoothly, the generation of by-products and impurities is further avoided, the purity of the CuBi2O4 product is improved, and the catalytic performance and catalytic rate of the composite photocatalyst are further improved.

[0043] After the hydrothermal reaction is completed, the present invention preferably centrifuges and dries the product of the hydrothermal reaction in sequence to obtain CuBi2O4.

[0044] The present invention has no special limitation on the centrifugation and drying operations, and the solid product can be separated by the operations commonly used by those skilled in the art.

[0045] In the present invention, the copper source is preferably copper nitrate or copper sulfate, more preferably copper nitrate. In the present invention, the copper source provides Cu element as a raw material for synthesizing CuCo2O4.

[0046] In the present invention, the cobalt source is preferably cobalt nitrate or cobalt chloride, more preferably cobalt nitrate. In the present invention, the cobalt source provides Co element as a raw material for synthesizing CuCo2O4.

[0047] In the present invention, the solvent is preferably one or more of methanol, ethanol and isopropanol, more preferably ethanol. In the present invention, the solvent ensures that the reaction raw materials can be completely dissolved and the chemical reaction can proceed smoothly.

[0048] In the present invention, the molar ratio of CuBi2O4, copper source, cobalt source and urea is preferably 1:(1-3):(4-6):(1-3); more preferably 1:(1.5-2.5):(4.5-5.5):(1.5-2.5), and most preferably 1:2:5:2. In the present invention, by controlling the amount ratio of the reaction raw materials, sufficient reaction between the reaction raw materials is ensured, while the thermal motion of the raw materials and products in the reaction system is intensified, and the mixing of the components in the mixed solution system is promoted; at the same time, by controlling the amount ratio of the raw materials, the molar ratio of CuBi2O4, CuCo2O4 and BiOF in the obtained composite photocatalyst can be ensured to be within the range of 1:(0.05-6.0):(0.02-0.12).

[0049] In the present invention, the ratio of the amount of the substance of CuBi2O4 to the volume of the solvent is preferably (1-5) mmol:40mL, more preferably (1-3) mmol:40mL, and most preferably 1 mmol:40mL; the concentration of ammonium fluoride in the mixed solution is preferably 5-30mmol / L, more preferably 10-25mmol / L, and most preferably 15-20mmol / L. In the present invention, by controlling the concentration of the reaction raw materials, the generation of the products CuCo2O4 and BiOF is promoted, and it is ensured that the product CuCo2O4 / BiOF / CuBi2O4 composite photocatalyst can be obtained; at the same time, the components of the composite material can have a tighter interface, the interfaces can have a stronger interaction, and a double interface structure can be formed between the three components in the catalyst, thereby constructing multiple ion carrier diversion channels, providing more transmission paths for photogenerated carriers, promoting efficient separation of carriers, and further improving the catalytic performance and catalytic efficiency of the composite photocatalyst; and by controlling the concentration of the reaction raw material ammonium fluoride , the morphology of the composite catalyst can be controlled to a certain extent, providing a larger specific surface area and more reaction sites, improving the light capture efficiency of the composite catalyst, and further improving the catalytic performance; controlling the morphology of the composite catalyst can also provide more transmission channels for photogenerated carriers, improve the separation efficiency, and further improve the catalytic efficiency; by controlling the ratio of the amount of CuBi2O4 to the volume of the solvent and the concentration of ammonium fluoride, the amount of CuBi2O4, CuCo2O4 and BiOF in the composite photocatalyst is further guaranteed to be in the range of 1: (0.05 ~ 6.0): (0.02 ~ 0.12).

[0050] After obtaining the mixed solution, the present invention performs a solvothermal reaction on the mixed solution to obtain a precursor.

[0051] In the present invention, the temperature of the solvent thermal reaction is preferably 100-180°C, more preferably 120-160°C, and most preferably 135-150°C; the time of the dissolution thermal reaction is preferably 2-24h, more preferably 3-15h, and most preferably 6h. In the present invention, by controlling the process parameters of the dissolution thermal reaction, the generation of the products CuCo2O4 and BiOF is ensured, and the catalytic activity and catalytic rate of the composite catalyst are further improved.

[0052] After the solvothermal reaction is completed, the present invention preferably centrifuges the product of the solvothermal reaction to obtain a precursor.

[0053] The present invention has no special limitation on the centrifugal operation, and the solid product can be separated by the commonly used operation by those skilled in the art.

[0054] After obtaining the precursor, the present invention calcines the precursor to obtain a composite photocatalyst.

[0055] In the present invention, the calcination temperature is preferably 300-500°C, more preferably 350-450°C, and most preferably 380-400°C; the calcination heating rate is preferably 1-10°C / min, more preferably 3-8°C / min, and most preferably 5-6°C / min; the calcination time is preferably 0.5-8h, more preferably 2-6h, and most preferably 4-5h. In the present invention, by controlling the process parameters of calcination, the crystal structures of the three components in the composite material are gradually formed and improved, and components with specific morphologies are formed, thereby obtaining nanorod-shaped CuBi2O4 and nanosheet-shaped CuCo2O4; the in-situ growth of CuCo2O4 and BiOF on the surface of CuBi2O4 is promoted, so that a tighter interface is formed between the three, chemical bonds are formed and electrons are transferred at the interface, and a strong interface interaction is generated, thereby constructing multiple ion-carrier shunt channels, providing more transmission paths for photogenerated carriers, enabling the photogenerated carriers to migrate to the reaction active sites of the catalyst more quickly and effectively, and further improving the catalytic activity and catalytic efficiency of the composite photocatalyst.

[0056] The preparation method of the composite photocatalyst provided by the present invention is simple. Through solvent thermal reaction and calcination reaction, the in-situ growth of CuCo2O4 and BiOF on the surface of CuBi2O4 is achieved, multiple ion carrier diversion channels are constructed, more transmission paths are provided for carriers and recombination between carriers is avoided, thereby further improving the catalytic performance of the composite photocatalyst.

[0057] The present invention also provides the use of the composite photocatalyst described in the above technical solution or the composite photocatalyst prepared by the preparation method described in the above technical solution in catalytic degradation of organic pollutants in sewage.

[0058] In the present invention, the dosage of the composite photocatalyst is preferably 1-5 g / L, more preferably 1-3 g / L, and most preferably 1 g / L; the concentration of organic pollutants in the sewage is preferably 50-1000 mg / L, more preferably 50-500 mg / L, and most preferably 50 mg / L; the composite photocatalyst is preferably activated with potassium thiosulfate when used; the mass ratio of the composite photocatalyst to potassium thiosulfate is preferably 1:(3.8-19), more preferably 1:(3.8-10), and most preferably 1:3.8. In the present invention, by limiting the use conditions and dosage of the composite photocatalyst, it is ensured that the composite photocatalyst can achieve sufficient catalytic degradation of organic pollutants.

[0059] The present invention helps the composite photocatalyst to fully contact with the organic pollutants in the wastewater by controlling the conditions of the composite photocatalyst application process, thereby improving the catalytic activity and catalytic efficiency of the composite photocatalyst.

[0060] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] Example 1

[0062] A composite photocatalyst, comprising CuBi2O4 and CuCo2O4 and BiOF in situ grown on the CuBi2O4;

[0063] The CuBi2O4 is a nanorod, the length of the nanorod is 200nm-3μm, and the diameter is 30-70nm;

[0064] The preparation method of the composite photocatalyst comprises the following steps:

[0065] (1) 2 mmol of copper nitrate, 4 mmol of bismuth nitrate and 18 mmol of sodium hydroxide were stirred and mixed with 75 mL of water for 2 h to obtain a first mixed solution; wherein the molar ratio of copper nitrate, bismuth nitrate and sodium hydroxide was 1:2:9; and the molar ratio of copper nitrate to the volume of water was 1 mmol:37.5 mL;

[0066] (2) transferring the first mixed solution obtained in step (1) to a hydrothermal reactor, performing a hydrothermal reaction at 180° C. for 24 h, and centrifugally drying to obtain CuBi2O4;

[0067] (3) 1 mmol of the CuBi2O4 obtained in step (2) is mixed with 0.5 mmol of copper nitrate, 0.5 mmol of cobalt nitrate, 2.5 mmol of urea, 1 mmol of ammonium fluoride and 40 mL of ethanol to obtain a second mixed solution, wherein the molar ratio of CuBi2O4, copper nitrate, cobalt nitrate and urea is preferably 1:2:5:2; the molar ratio of CuBi2O4 to the volume of ethanol is 1 mmol:40 mL; and the concentration of ammonium fluoride is 20 mmol / L;

[0068] (4) subjecting the second mixed solution obtained in step (3) to a solvothermal reaction at 150° C. for 6 hours to obtain a precursor;

[0069] (5) Calcine the precursor obtained in step (4) at 300° C. for 1 h, wherein the calcination heating rate is 3° C. / min, to obtain a composite photocatalyst.

[0070] The composite photocatalyst of Example 1 was detected by scanning electron microscopy, and the obtained SEM image is as follows: Figure 1 As shown. Figure 1 It can be seen that the surface of the CuBi2O4 nanorods is closely grown with surface-dense nanosheets of CuCo2O4 and BiOF.

[0071] Example 2

[0072] A composite photocatalyst, comprising CuBi2O4 and CuCo2O4 and BiOF in situ grown on the CuBi2O4;

[0073] The CuBi2O4 is a nanorod, the length of the nanorod is 200nm-3μm, and the diameter is 30-70nm;

[0074] The difference between Example 2 and Example 1 in the preparation method of the composite photocatalyst is that the amount of ammonium fluoride is increased so that the concentration of ammonium fluoride in the second mixed solution in step (3) is 30 mmol / L, and the rest is the same as Example 1.

[0075] The composite photocatalyst of Example 2 was detected by scanning electron microscopy, and the obtained SEM image is as follows: Figure 2 As shown. Figure 2 It can be seen that fluffy nanosheets CuCo2O4 and BiOF grow on the surface of nanorods CuBi2O4.

[0076] Example 3

[0077] A composite photocatalyst, comprising CuBi2O4 and CuCo2O4 and BiOF in situ grown on the CuBi2O4;

[0078] The CuBi2O4 is a nanorod, the length of the nanorod is 200nm-3μm, and the diameter is 30-70nm;

[0079] The only difference between Example 3 and Example 2 in the preparation method of the composite photocatalyst is that the concentration of ammonium fluoride in the second mixed solution in step (3) is 25 mmol / L, and the rest is the same as Example 2.

[0080] The composite photocatalyst of Example 3 was detected by scanning electron microscopy, and the obtained SEM image is as follows: Figure 3 As shown. Figure 3 It can be seen that relatively fluffy nanosheets CuCo2O4 and BiOF are densely grown on the surface of nanorods CuBi2O4.

[0081] Comparative Example 1

[0082] A CuBi2O4 photocatalyst;

[0083] The preparation method of the CuBi2O4 photocatalyst comprises the following steps:

[0084] (1) 2 mmol of copper nitrate, 4 mmol of bismuth nitrate, and 18 mmol of sodium hydroxide were stirred and mixed with 75 mL of water for 2 h to obtain a mixed solution;

[0085] (2) The mixed solution obtained in step (1) was transferred to a hydrothermal reactor, subjected to a hydrothermal reaction at 180° C. for 24 h, and centrifuged to obtain a CuBi2O4 photocatalyst.

[0086] Comparative Example 2

[0087] A CuCo2O4 photocatalyst;

[0088] The preparation method of the CuCo2O4 photocatalyst comprises the following steps:

[0089] (1) 0.5 mmol copper nitrate, 0.5 mmol cobalt nitrate, 2.5 mmol urea and 50 mL ethanol were mixed to obtain a mixed solution;

[0090] (2) subjecting the mixed solution obtained in step (1) to a solvothermal reaction at 150° C. for 6 h to obtain a CuCo2O4 photocatalyst.

[0091] The composite photocatalyst of Example 2, the CuBi2O4 photocatalyst of Comparative Example 1 and the CuCo2O4 photocatalyst of Comparative Example 2 were tested by X-ray diffractometer, and the obtained XRD patterns are as follows: Figure 4 As shown. Figure 2 It can be seen that the CuCo2O4 / BiOF / CuBi2O4 composite photocatalyst of Example 2 presents diffraction signals of CuCo2O4, CuBi2O4 and BiOF, indicating that the composite catalyst contains CuCo2O4, BiOF and CuBi2O4 components; and by comparing with the standard card, it can be known that the comparison card number of BiOF in the composite catalyst is JCPDS No.73-1579; no diffraction peaks of other impurities are detected in the composite, indicating that the prepared CuCo2O4 / BiOF / CuBi2O4 composite photocatalyst has a high purity.

[0092] Application Example 1

[0093] Take 50 mg of the composite photocatalyst of Examples 1 to 3, 50 mg of the CuBi2O4 photocatalyst of Comparative Example 1, and 50 mg of the CuCo2O4 photocatalyst of Comparative Example 2, respectively, and add them into 50 mL of a tetracycline hydrochloride solution with an initial concentration of 50 mg / L, and add 1 mM potassium thiosulfate for activation.

[0094] The catalytic activity of the CuCo2O4 / BiOF / CuBi2O4 composite photocatalysts in Examples 1 to 3, the CuBi2O4 photocatalyst in Comparative Example 1, and the CuCo2O4 photocatalyst in Comparative Example 2 to tetracycline hydrochloride is shown in the figure. Figure 5 As shown. Figure 5 It can be seen that the CuCo2O4 / BiOF / CuBi2O4 composite photocatalyst can degrade 90.3% of tetracycline hydrochloride in 15 minutes, and its catalytic degradation activity and catalytic degradation rate are significantly higher than those of the CuBi2O4 photocatalyst and the CuCo2O4 photocatalyst; indicating that the composite photocatalyst provided by the present invention has excellent catalytic activity and high catalytic efficiency.

[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite photocatalyst comprising CuBi2O4 and CuCo2O4 and BiOF in situ grown on the CuBi2O4.

2. The composite photocatalyst according to claim 1, characterized in that: The CuBi2O4 is a nanorod; the length of the nanorod is 200nm-3μm, and the diameter is 30-70nm.

3. The method for preparing the composite photocatalyst according to any one of claims 1 to 2, comprising the following steps: (1) mixing CuBi2O4 with a copper source, a cobalt source, urea, ammonium fluoride and a solvent to obtain a mixed solution; (2) subjecting the mixed solution obtained in step (1) to a solvothermal reaction to obtain a precursor; (3) calcining the precursor obtained in step (2) to obtain a composite photocatalyst.

4. The preparation method according to claim 3, characterized in that: The molar ratio of CuBi2O4, copper source, cobalt source and urea in step (1) is 1:(1-3):(4-6):(1-3).

5. The preparation method according to claim 3, characterized in that: The ratio of the amount of CuBi2O4 in step (1) to the volume of the solvent is (1-5) mmol:40 mL.

6. The preparation method according to claim 3, characterized in that: The concentration of ammonium fluoride in the mixed solution in step (1) is 5 to 30 mmol / L.

7. The preparation method according to claim 3, characterized in that: The temperature of the solvent thermal reaction in step (2) is 100 to 180° C., and the time of the dissolution thermal reaction is 2 to 24 hours.

8. The preparation method according to claim 3, characterized in that: In the step (3), the calcination temperature is 300-500° C., the calcination heating rate is 1-10° C. / min, and the calcination time is 0.5-8 h.

9. Use of the composite photocatalyst according to any one of claims 1 to 2 or the composite photocatalyst prepared according to the preparation method according to any one of claims 3 to 8 in catalytic degradation of organic pollutants in sewage.

10. The use according to claim 9, characterized in that: The dosage of the composite photocatalyst is 1-5 g / L.